Mathematical Critical Thinking Ability and Learner's Responsibility Character in Learning Cycle 7E with Scaffolding (Universitas Negeri Semarang, 2021)
This research aims to describe the critical thinking ability of mathematical and the character of the responsibility of learners in learning cycle 7E with scaffolding. This research is a type of research combined with concurrent embedded type. Data collection of critical thinking ability is done using the mathematical critical thinking ability test. The character data of responsibility is obtained from the results of the questionnaire of the character of responsibility. The results showed that the quality of LC7E learning with Scaffolding is (1) at the planning stage, the research instruments that had been compiled are valid, (2) at the implementation stage, had well-categorized learning results and get positive responses from learners, and (3) at the assessment stage, meet the effectiveness test. Also, learners with high responsibility characters can achieve six indicators of mathematical critical thinking ability, learners with moderate responsibility characters have varying mathematical critical thinking abilities that are capable of all six indicators of critical thinking ability and some were only capable at four indicators of mathematical critical thinking ability, while learners with low responsibility characters had not been able to achieve six indicators of mathematical critical thinking ability.